Transient Analysis of EVA Foam Damping and Spatial Optimization of FSR Sensors on Shain Guards - Fahrizal Akbar Herbhakti; Africo Ramadhani; Erny Amalia Lestari; Azry Ayu Nabilah; Muhamad Ihsan Hufadz (PT FORMOSA CENDEKIA GLOBAL, 2026)
Embedding Force Sensitive Resistors (FSR) into EVA foam for smart shin guards is hindered by stiffness mismatch between the soft matrix and rigid sensor. This study determines the optimal embedment depth that balances signal fidelity and structural integrity. Coupled multiphysics FEM simulations (COMSOL) employing a hyper elastic Mooney-Rivlin model and piezoresistive equations were run under a 1500 N peak Gaussian impact pulse. At 2 mm depth, sensitivity reached –85% ΔR but shear stress peaked at a critical 42.5 MPa; 8 mm depth was very safe (12.4 MPa) but gave a weak –25% ΔR. The optimum depth was 5 mm, yielding 24.8 MPa shear stress, –62% sensitivity, 2.5 ms latency, and high SNR. Sensitivity analysis and numerical optimization confirmed this sweet-spot. The computational framework provides precise parameters for manufacturing IoT-enabled smart shin guards.